The Bravest Dog Ever: The True Story of Balto - Standiford, Natalie; Cook, Donald (New York : Random House, 1989)
Recounts the life of Balto, the sled dog who saved Nome, Alaska in 1925 from a diphtheria epidemic by delivering medicine through a raging snowstorm.
Keywords: Balto (Dog) -- Juvenile literature; Sled dogs -- Biography -- Alaska; Diphtheria -- Prevention -- Alaska; Balto (Dog); Sled dogs; Dogs; Diphtheria -- Alaska; Alaska -- History